2014
DOI: 10.1200/jco.2014.32.26_suppl.44
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Angelina Jolie's (AJ) story on genetic referral and testing at an academic cancer centre.

Abstract: 44 Background: In May 2013, AJ revealed to the media that she had undergone preventive double mastectomy. The actress had a family history of breast and ovarian cancer and tested positive for the BRCA1 gene mutation. Media coverage has been extensive, but it’s not clear what messages the public and professional medical staff took from this personal story that sometimes could be misleading. Methods: We conducted a retrospective review in our centre using data from the clinical database of the Familial Cancer P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…9 A recent Canadian study described a similar, dramatic increase in both counseling and testing when comparing referral patterns in the 6 months before the Jolie op-ed was published to the 6 month period following publication. 10 …”
Section: Discussionmentioning
confidence: 99%
“…9 A recent Canadian study described a similar, dramatic increase in both counseling and testing when comparing referral patterns in the 6 months before the Jolie op-ed was published to the 6 month period following publication. 10 …”
Section: Discussionmentioning
confidence: 99%
“…In the Canadian study, a 90% increase among women correctly referred for breast cancer genetic counseling after media reports was observed. 15 In the UK study, the referrals more than doubled after Ms. Jolie's announcement, and remained at this level for at least 6 months thereafter. 11 We found that the media-related effect triggered awareness regardless of the level of personal involvement of the participants.…”
Section: Public Awareness In Breast Cancer/lebo Et Almentioning
confidence: 89%
“…To our knowledge, only a few publications to date have highlighted the media‐related impact on the health care sector, notably breast cancer. Two retrospective studies, one from Canada and one from the United Kingdom, demonstrated that referral rates for breast cancer were influenced by the media‐related publication of Ms. Jolie's prophylactic bilateral mastectomy in May 2013. In the Canadian study, a 90% increase among women correctly referred for breast cancer genetic counseling after media reports was observed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This announcement led to what oncologists refer to as “The Angelina Jolie Effect,” a more than doubling in the demand for BRCA testing in women who would not otherwise have gone for testing, but were at high risk for carrying the mutation based on family history and therefore should have undergone genetic testing. 2 In March 2015, Angelina Jolie published a second op-ed in The New York Times disclosing that she had undergone laparoscopic oophorectomy, removal of the ovaries to prevent ovarian cancer, and that she was receiving hormone replacement therapy to prevent the side-effects of premature menopause. 3…”
Section: Introductionmentioning
confidence: 99%